2020
DOI: 10.1057/s41262-020-00193-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of passion/determination and external disadvantage on consumer responses to brand biographies

Abstract: Brands frequently convey their stories in brand biographies in order to elicit positive consumer responses. This article examines the influence of consumers' perceptions of passion/determination and external disadvantage reflected in brand biographies on narrative transportation, consumers' post-message engagement, and purchase intentions. Results suggest that passion/determination affects purchase intentions positively, both directly and through narrative transportation and post-message engagement. External d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…An ANOVA confirmed that the underdog brand was perceived as more externally disadvantaged and lacking resources (M underdog = 5.03, SD = 1.56 vs. M topdog = 1.69, SD = 1.03; F(1, 115) = 188.16, p < .01, ɳ 2 = .621), and as more passionate and determined (M underdog = 6.51, SD = .81 vs. M topdog = 5.76, SD = 1.04; F(1, 115) = 18.81, p < .01, ɳ 2 = .141). Although the topdog brand biography's passion/determination mean score was above scale midpoint ( 4), support for a successful manipulation based on a significant difference between the brand biographies on this dimension is consistent with prior literature (Delgado-Ballester, 2020;Grohmann & Nguyen, 2020;Nagar, 2020).…”
Section: Brand Biographysupporting
confidence: 79%
See 2 more Smart Citations
“…An ANOVA confirmed that the underdog brand was perceived as more externally disadvantaged and lacking resources (M underdog = 5.03, SD = 1.56 vs. M topdog = 1.69, SD = 1.03; F(1, 115) = 188.16, p < .01, ɳ 2 = .621), and as more passionate and determined (M underdog = 6.51, SD = .81 vs. M topdog = 5.76, SD = 1.04; F(1, 115) = 18.81, p < .01, ɳ 2 = .141). Although the topdog brand biography's passion/determination mean score was above scale midpoint ( 4), support for a successful manipulation based on a significant difference between the brand biographies on this dimension is consistent with prior literature (Delgado-Ballester, 2020;Grohmann & Nguyen, 2020;Nagar, 2020).…”
Section: Brand Biographysupporting
confidence: 79%
“…The brand biography literature empirically supports that brand biographies trigger narrative transportation and positive consumer responses, consistent with the extended transportation-imagery model (Delgado-Ballester, 2020;Nguyen & Grohmann, 2020;Tezer et al, 2019). Congruence between brand biographies and consumers' self-concept is also a strongly supported antecedent of narrative transportation (Delgado-Ballester, 2020; Tezer et al, 2019).…”
Section: Brand Biographies and The Extended Imagery-transportation Modelmentioning
confidence: 60%
See 1 more Smart Citation
“…Nguyen et al pointed out that it is necessary to improve brand awareness through external brand communication and brand embodiment [5]. Chun et al analyzed from other perspectives and divided brand awareness into two research points: (i) brand memory and (ii) brand recognition [6].…”
Section: Related Workmentioning
confidence: 99%
“…Based on the research presented in this article, a number of recommendations for the management of underdog brands can be derived in practice, which results directly from the Underdog Brand Management Framework (see Table 4). We would like to point out the five most important of these practical implications from our point of view: Firstly and maybe most important, underdog brand biographies are effective brand marketing tools (Paharia et al 2011;Staton et al 2012) and the competitive narrative-its battle with a large competitor and its determination in overcoming the external disadvantages-should be made salient (Nguyen and Grohmann 2020). Therefore, we would like to recommend that the managers of underdog brands reflect on the key data of an organisation's origins, translate this data into a rather dramatic founding story and express it on the company website and at other suitable brand touchpoints (e.g., through regular postings on social media, in a company brochure, in the entrance area of the company buildings, via other channels of marketing communication).…”
Section: Implications For Theory and Practicementioning
confidence: 99%